2014
DOI: 10.1161/circep.113.000805
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation Versus Antiarrhythmic Medication for Treatment of Ventricular Premature Beats From the Right Ventricular Outflow Tract

Abstract: a total of 513 consecutive patients who were referred to the Second Affiliated Hospital of Chongqing Medical University for treatment of RVOT VPBs were © 2014 American Heart Association, Inc. Original ArticleBackground-The purpose of this study was to compare the efficacy of radiofrequency catheter ablation (RFCA) versus antiarrhythmic drugs (AADs) for treatment of patients with frequent ventricular premature beats (VPBs) originating from the right ventricular outflow tract (RVOT). Methods and Results-A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 31 publications
6
135
0
10
Order By: Relevance
“…Friedman et al [14] have reported the success of ablation in 9 of 10 patients with non-inducible VT originating from the RVOT. Ling et al [16] reported superiority of RFA over antiarrhythmic medication in arrhythmia suppression in patients with RVOT PVCs, in a prospective randomized study. Zhang et al [17] found NCMS--guided RVOT catheter ablation highly effective, and clinical success was best achieved by ablating the EA site, rather than BO site.…”
Section: Discussionmentioning
confidence: 99%
“…Friedman et al [14] have reported the success of ablation in 9 of 10 patients with non-inducible VT originating from the RVOT. Ling et al [16] reported superiority of RFA over antiarrhythmic medication in arrhythmia suppression in patients with RVOT PVCs, in a prospective randomized study. Zhang et al [17] found NCMS--guided RVOT catheter ablation highly effective, and clinical success was best achieved by ablating the EA site, rather than BO site.…”
Section: Discussionmentioning
confidence: 99%
“…13,33 In two-thirds of the patients undergoing PVC ablation due to PVC-mediated cardiomyopathy, LV function improves to normal within 4 months, although in some cases it takes more than a year. 33,38,39 Recurrence after successful ablation is possible due to remodeling of the arrhythmogenic substrate or reconnection to exit sites.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these shortcomings, patients may choose to pursue catheter ablation of PVCs implicated in causing symptoms, ventricular tachyarrhythmia, or cardiomyopathy. 38,39 According to the American College of Cardiology/American Heart Association/European Society of Cardiology 2006 Guidelines, PVC ablation is reasonable (Class IIa) for symptomatic PVCs when drug therapy is ineffective, not tolerated, or not preferred by the patient. PVC ablation may also be considered (Class IIb) to treat or prevent PVC-mediated cardiomyopathy or for fascicular system PVCs that reproducibly induce ventricular fibrillation (Table 3).…”
Section: Ablation Versus Medical Therapymentioning
confidence: 99%
“…5 However, the complex 3-dimensional anatomic relationships between different adjacent structures in the right and left ventricular OTs pose substantial difficulties to mapping and ablation of VAs arising from this region. [7][8][9] The reasons underlying ablation failure are multifactorial and include lack of accurate localization because of minimal ectopy available to map, 10 safety concerns with ablation at the target site(s), 7,11 recurrence of different VAs, 4 and inability to access critical sites for mapping or ablation.…”
Section: See Article By Yamada Et Almentioning
confidence: 99%
“…The traditional belief that these arrhythmias have an entirely benign prognosis and excellent response to therapy with antiarrhythmic drugs and catheter ablation has been challenged by recent evidences reporting the presence of localized concealed cardiomyopathic substrates in many of these patients 1,2 and large epidemiological studies showing an independent longitudinal association between VAs and the risk of heart failure and death, 3 together with the disappointing results of randomized trials testing VA suppression with antiarrhythmic drug therapy and long-term catheter ablation outcome data from experienced centers reporting a recurrence rate of ≤30%. 4,5 Although there are patients with no arrhythmia-related symptoms and normal left ventricular function who do not derive benefit from VA suppression regardless of the VA burden, achievement of durable VA suppression represents a relevant therapeutic end point to improve quality of life when arrhythmia-related symptoms are present 4 or to reverse left ventricular systolic dysfunction in patients with VA-induced cardiomyopathy. 6 …”
mentioning
confidence: 99%